Influência da precipitação de sulfato de bário na permeabilidade de meios porosos - Dornelas, Vitoria Felicio (2020)
Whit intensified and accelerated population growth and increased energy demand, it is necessary to ensure the oil production flow. To do so, the oil sector must overcome some challenges, such as ultra deep waters and extensively pre salt layers, and the problems associated with them. One of the main problems encountered is inorganic scales that can occur throughout the production chain, from the reservoir to surface. In particular, its occurrence in the “near well” region have a more intense impact on fluids production, since the removal or formation inhibition of the salt in this region is more complex. The most commonly inorganic scale founded in this region is barium sulphate. The study of this scale inside the porous medium is important, since it presents the lowest solubility and occurs through incompatibility between ions present in water formation and injection fluids. This experimental work look to monitor the barium sulphate precipitation effects on petrophysical parameters, like porosity and permeability, of sinthetics sandstone samples, kind of Berea Buff, Berea and Zebra.To observe the scale impact, the methodology proposes to use a 250ppm barium chloride solution, to represent water formation and a 2750ppm sodium sulphate solution to represent the injection fluid. The procedure involved porous medium characterization before and after the scale test . Potassium chloride solution was used to characterized the porous medium samples. The flow behavior during characterizations tests were Darcyano, allowing the use of Darcy’s Law to calculate permeability. The behavior of pressure through time was measured throughout the procedure. The scale tests were executed for 4 to 6 porous volumes, where the produced fluid passes through electrical conductivity measurements and chloride titration, which indirectly will be used to estimate the precipitated mass of barium sulphate. However, the cleaning methodology wasn’t efficient to remove all chloride from the characterization fluid of the sample. Was noted that, as the porous medium permeability reduces (Berea Buff > Berea > Zebra) the residual chloride ions and conductivity increased. As the flowing through the sample gets difficult, the cleaning procedure becomes ineffective. With that, was found residual potassium chloride on the samples 1,5% of KCl in mass on Zebra, 0,5% on Berea and < 0,5% on Berea Buff. So, the cleaning procedure shown to be ≅80% efficiency to Berea Buff samples, ≅50% efficiency on Berea samples and between 0 to 50% eficiente on Zebras samples. As the barium sulphate mass quantification would be realized indirectly the chloride presence from the potassium chloride solution made impractical the calculation of barium sulphate mass. The porosity and permeability results showed that the sample were influenced by the scale test, by damage, permeability reduction ou stimulus, permeability increase. The porous medium Berea Buff, presented a tendency to permeability reduction in all samples. The porou medium Berea, shown a increase of permeability on samples 1 and 3. And the porous medium Berea showed damage on samples 2 and 4, and stimulus on samples 1 and 3, those last ones had elevated injection pressure. Anyway, it was noted that the use of potassium chloride solution minimizes the effects of shale swelling and permits that the flow behaves as Darcyan on the porous medium. This study, however, was not appropriate to determine the barium sulphate precipitated mass. The initial concentration of barium ions were low, to make an expressive effect and the barium indirect quantification, by titration of chloride ions, was not appropriated, because of the inefficiency of the cleaning procedure